Long-Term Performance of a Pilot Scale Combined Chemical Precipitation-Ultrafiltration Technique for Waste Brine Regeneration at Chevron Steam Flooding Plant - I Gede Wenten; Khoiruddin Khoiruddin; Ahmad Nurul Hakim; Putu T.P. Aryanti; Nengsi Rova (Institute for Research and Community Services, Institut Teknologi Bandung, 2020)
In this work, chemical precipitation-ultrafiltration (UF) was applied for waste brine regeneration from a steam flooding plant at Duri Field, Chevron. A mixture of sodium hydroxide and sodium carbonate solution was used as chemical agent. A polypropylene (PP) UF membrane was used to remove precipitate formed in the chemical precipitation. It was found that the combined process could be used to regenerate waste brine, removing up to 100% (±0.1) of calcium and up to 99.6% (±0.3) of magnesium. High hardness removal was achieved when the chemical dosage was 1.3 to 1.7 mole of chemical/mole of hardness. Rapid permeability decline was observed in the UF membrane due to the high turbidity and TSS values of the chemically treated waste brine. Backwash with an acid solution could recover the UF membrane's permeability effectively. However, pH adjustment is needed due to the high pH value of the UF permeate (up to 12).